Pengaruh variasi suhu karbonisasi terhadap mikrostruktur dan derajat kristalinitas karbon aktif kulit singkong sebagai bahan dasar GDL (Gas Diffussion Layer) (The effect of variations in carbonization temperature on the microstructure and degree of crystallinity of the activated carbon of cassava peels as the basic material of GDL (Gas Diffusion Layer)) - Vathasia Kartika (Department of Physics – Universitas Negeri Padang UNP, 2016)
The energy crisis is an old problem that has continued until today. Fuel Cell is one answer to solve the problem of this energy crisis. One type of fuel cell that is growing up now is the PEMFC (Proton Exchange Membrane Fuel Cell). The main components that play an important role in the PEMFC is the GDL (Gas Diffussion Layer). GDL important role in the electron transfer process, so the material must essentially activated carbon which has a high absorption. Activated carbon is commonly used CNT (Carbon Nano Tube) are hard to get and expensive. Peel cassava is one of the alternative carbon sources that can be processed into activated carbon. This study aims to determine the effect of carbonization temperature on the microstructure and the degree of crystallinity of activated carbon cassava peel. Variations carbonization temperature are 300 0C, 400 0C and 500 0C. Activated carbon microstructure characterization of cassava peel is done with SEM (Scanning Electron Microscopy), while the characterization of the degree of crystallinity is done by XRD (X-Ray Diffraction). The results showed that the size of the pores formed is still relatively macropore is greater than 0.5 micrometers, whereas the calculation of the degree of crystallinity for each of the various samples were 36.64%, 30.20% and 30.54%. Shell activated carbon potential of cassava as a raw material GDL is based on the degree of crystallinity, but still do not meet the standards based microstructures are formed